Distribution of ancient landslides and landslide hazard assessment in the Western Himalayan Syntaxis area - Cui, Yulong; Yang, Wenhao; Xu, Chong; Wu, Shuai (Frontiers in Earth Science, 2023)
The Western Himalayan Syntaxis area is located near the Pamir Plateau. The geological structure is active, and geological disasters occur frequently in this area. In this study, we employed the Google Earth platform and artificial visual interpretation to identify ancient landslides in the region and to establish a regional ancient landslide database. Then, nine landslide-influencing factors (elevation, slope, aspect, curvature, distance to the water system, distance to a glacier, stratum lithology, distance to a fault, and distance to the epicenter of earthquakes above magnitude 5) were examined using the ArcGIS software platform. The spatial distribution characteristics of landslides were analyzed statistically. Finally, an IV model and WoE model were used to evaluate the regional landslide hazard, and the evaluation results were verified via a confusion matrix and a receiver operating characteristic (ROC) curve. The results showed that there were 7947 landslides in this area, with a total area of 3747.27 km2. Landslides were mostly developed at an elevation of 4000–5000 m, a slope of 15–25°, a north aspect, curvature of –0.33 to 0.33, distance to the water system of 1000–2000 m, distance to a glacier of 2000–5000 m, stratigraphic lithology Permian (P) and Triassic (T), and distance to a fault of 20,000–50,000 m. The evaluation accuracy of the IV and WoE models was relatively high. The comprehensive accuracy of the confusion matrix of the two models was above 70%, and the AUC value of the ROC curve was above 75%. The landslide database of the Western Himalayan Syntaxis landslide established in this paper as well as the landslide distribution law and hazard assessment results obtained can provide a reference for landslide disaster prevention and mitigation and engineering construction planning in this area.